Experimnetal Investigation on Outdoor and Indoor PM2.5 and PM10 in Supermarkets in Bandung During Covid-19 Pandemic - Kasni Sumeru; Toto Tohir; Neni Emrida Panjaitan; Mohamad Firdaus bin Sukri (Jurnal Internasional Penelitian Teknologi Terapan, 2021)
During the Covid-19 pandemic, the number of visitor at the trade center in Bandung was much reduced as compared to before pandemic, which was only about 30% of normal conditions. The present study is to investigate particulate concentrations of PM2.5 and PM10 in three supermarkets in Bandung, namely Kosambi, Batununggal Modern and Cinunuk supermarkets during the pandemic of Covid-19. Air sampling was measured using a particulate counter CEM DT96 for 11 hours, from 06:00 AM to 5:00 PM, local time. The results showed that the average of outdoor and indoor concentrations of PM10 in two supermarkets (Batununggal Modern and Griya Cinunuk) was lower than standard during that 11 hours. As for the outdoor concentrations of PM2.5, both markets exceeded the standard for several hours in the morning. In general, it can be concluded that the outdoor and indoor concentrations of PM2.5 and PM.10 during pandemic were below the standard, except in the morning before 10:00 AM